EFFECTIVENESS OF COMPLEX TREATMENT OF PATIENTS WITH ACUTE PERITONITIS - Mahmuda N. Agzamova; Farhod D. Ortiqboyev (Central Asian Journal of Medicine, 2023)
In our research, we tested the effectiveness of complex treatment of patients with acute peritonitis with lymphotropic therapy with antibiotics and thymalin according to our method.